IMPLEMENTASI SUPERVISI PENDIDIKAN DI SMKS NAHDLATUL ULAMA TASIKMALAYA - Mu'awwanah, Muna Fathiyyatul; Halimah, Ai Hilyatul; Rahmawati, Wulan (Institut Nahdlatul Ulama Tasikmalaya, 2025)
Education is a conscious effort aimed at developing science and technology, outlook on life, life attitudes, and skills of individuals and groups to achieve maturity in society. Teachers as educators play an important role in developing the potential of learners, in accordance with Law No. 20/2003 on the National Education System which recognizes them as professionals. This research explores educational supervision at SMKS Nahdlatul Ulama Tasikmalaya, assessing how the implementation of supervision by principals affects teacher performance. Supervision was conducted by the principal, vice principal for curriculum, and certified senior teachers. The research method used is a qualitative survey with data collection techniques through in-depth interviews and observations.The results show that supervision at SMKS Nahdlatul Ulama has been well planned and implemented, although there are some areas that need improvement, such as budget allocation and communication effectiveness. Collaboration between supervisors and teachers, as well as school support, are the keys to successful supervision. The evaluation shows that supervision has a positive impact on improving the quality of learning and teachers' professionalism. In conclusion, the implementation of educational supervision by principals in SMKS Nahdlatul Ulama Tasikmalaya significantly affects teachers' performance and improves the quality of education in the school. The school principal